DOI: 10.29007/jw6h
|View full text |Cite
|
Sign up to set email alerts
|

Predicting high-cost patients by Machine Learning: A case study in an Australian private hospital group

Abstract: Healthcare is considered a data-intensive industry, offering large data volumes that can, for example, be used as the basis for data-driven decisions in hospital resource planning. A significant aspect in that context is the prediction of cost-intensive patients. The presented paper introduces prediction models to identify patients at risk of causing extensive costs to the hospital. Based on a data set from a private Australian hospital group, four logistic regression models designed and evaluated to predict c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…One expert even had the idea that "critical decisions may be highlighted or need to be confirmed by a third person" (E1). Decisions in clinical environments need to be questioned and verified as diseases vary and evolve over time (Eigner et al 2019;Zwaan and Singh 2015). Overall, we derived the following research proposition (RP):…”
Section: Future Research Agenda For Ismentioning
confidence: 99%
“…One expert even had the idea that "critical decisions may be highlighted or need to be confirmed by a third person" (E1). Decisions in clinical environments need to be questioned and verified as diseases vary and evolve over time (Eigner et al 2019;Zwaan and Singh 2015). Overall, we derived the following research proposition (RP):…”
Section: Future Research Agenda For Ismentioning
confidence: 99%
“…However, the matrix highlights that transferring previously gained knowledge of the application of AI within diagnostics to other research areas seems possible and advisable. It appears that most of the algorithms were already being used in the diagnosis of neurological/psychiatric diseases (10), followed by cardiovascular and gastrointestinal disorders (7), and urogenital diseases (7). Dermatological, infectious, metabolic, and pulmonary diseases (3) were the least examined.…”
Section: Distribution Of Articles By Categorymentioning
confidence: 99%
“…We distinguished the origin of datasets as self-retrieved information (37), using an existing database (51), medical data grounded on other studies (7), and not providing any details (31). The results showed that most of the studies did not reveal detailed information on the data origin or how the data were collected, including circumstances or contexts.…”
Section: Dataset Characteristics and Performance Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables such as age [ 7 , 11 , 13 , 14 ], current high healthcare utilization/costs [ 7 , 13 , 15 ], hospitalization [ 13 , 16 ], (number of) chronic conditions [ 13 , 15 ], social deprivation [ 11 , 13 ], patients general health status [ 11 , 14 ], mental disorders [ 13 , 14 ], obesity-related factors [ 7 , 11 ] and diabetes or cardiovascular disease indicators [ 7 ] were found to be important predictors for becoming a HCP. Tamang et al (2017) [ 6 ] found that about one third of HCPs remain HCPs for the forthcoming year, while Wodchis et al (2016) [ 1 ] found that about 30 percent remain HCP for the following two years, once they are currently HCPs.…”
Section: Introductionmentioning
confidence: 99%